2016
DOI: 10.1016/j.clinimag.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the extent of microcalcifications to predict the size of a ductal carcinoma in situ: comparison between tomosynthesis and conventional mammography

Abstract: OBJECTIVES The objective was to determine if digital tomosynthesis of the breast (DBT) assesses the extension of ductal carcinoma in situ (DCIS) with higher precision than mammography (MG). MATERIAL AND METHODS The local ethics committee approved this retrospective study including 26 patients with DCIS, which were rated by three radiologists. Statistics were performed using intraclass correlation (ICC) for interreader agreement and the Pearson correlation for correlation of MG and DBT. Standard of reference wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…However, DBT reconstructs images of any depth of the breast and displays 3D information, which eliminates the potential overlap of normal and pathological tissue and presents microcalcification lesions with the mass or structural distortion more clearly. Berger et al (2016) 30 indicated that application of DBT improves predictive probability of ductal carcinoma in situ by increased microcalcification lesion detection, which is consistent with our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, DBT reconstructs images of any depth of the breast and displays 3D information, which eliminates the potential overlap of normal and pathological tissue and presents microcalcification lesions with the mass or structural distortion more clearly. Berger et al (2016) 30 indicated that application of DBT improves predictive probability of ductal carcinoma in situ by increased microcalcification lesion detection, which is consistent with our study.…”
Section: Discussionsupporting
confidence: 93%
“…However, DBT reconstructs images of any depth of the breast and displays 3D information, which eliminates the potential overlap of normal and pathological tissue and presents microcalcification lesions with the mass or structural distortion more clearly. Berger et al (2016) 30 indicated that application of DBT improves predictive F I G U R E 2 Diagnostic accuracy of digital breast tomosynthesis (DBT) and full-field digital mammography (FFDM) in different gland types of microcalcification and microcalcifications with different pathological classifications. A, Frequencies of DBT and FFDM on different gland types of microcalcifications at 100% and 75%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Few studies compared pathologic tumor size to radiologic size using different radiologic modalities. [11][12][13][14][15][16][17][18] In a recent study, Yoo et al 11 studied the correlation of MRI and pathologic size in breast carcinomas. However, not every breast carcinoma patient gets an MRI.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Some authors looked into tumor size concordance with respect to different imaging modalities, but many of these studies were limited, either by small sample size; because only a specific type of tumor was considered based on the exclusion criteria; or because only highly specialized techniques such as magnetic resonance imaging (MRI) was used, which is not as widely available or used as ultrasonography (USG) in the assessment of the breast carcinomas. [10][11][12][13][14][15][16][17][18][19][20][21] Moreover, most studies considered a size difference of AE5 mm to be concordant, 11,13 which is significant enough to result in a change of stage classification in a considerable number of cases. We compared pathologic tumor size with ultra-sonographic (USG) size.…”
Section: Introductionmentioning
confidence: 99%